The artist and his model in an interior space - Varona, Jorge Luis, author; Dietemann, David L., advisor; Yust, Dave, 1939-, committee member; Twarogowski, Leroy A., committee member; Williams, Ron G., committee member; Levine, Frederick S., committee member (Colorado State University. Libraries, 1984)
An exploration of visual, psychological, and atmospheric qualities of the figure in an interior space relative to other objects and figures. There is also consideration of the space in relationship to the canvas which the viewer occupies in observing the paintings.
Keywords: space (art)